The Role of the Family in the Faith Formation of Children in GMIM Bukit Moria Tikala Baru : Peran Keluarga dalam Pembentukan Iman Anak di GMIM Bukit Moria Tikala Baru - Glory Imanuela Kabangunang; Lovia Tuegeh; Adriel Manginsihi; Imanuel Irfan Mongkaren; Ineke Marlien Tombeng; Evi Stans Evlin Tumiwa; Hendry C. M. Runtuwene; James Edward Lalira (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Abstract This study aims to examine the role of the family in shaping children's faith amid the challenges of the digital era, focusing on the congregation of GMIM Bukit Moria Tikala Baru. Using a qualitative approach with an intrinsic case study design, the research collected data through open-ended questionnaires from 15 parents and 5 children, supplemented by interviews, limited observations, and document analysis. Thematic analysis was employed to identify patterns of spiritual practices, challenges, and children’s perceptions of faith transmission within the family. The findings show that the family serves as the first and primary community of faith, with prayer emerging as the dominant foundation in early faith formation. Nine out of fifteen parents mentioned teaching prayer as the initial step, followed by fostering regular church attendance and sharing Bible stories. Daily spiritual practices—such as morning prayers, prayers before meals, and evening prayers—are consistently carried out by most families, although formal family worship remains limited. The main challenges identified include the penetration of digital technology and social media (reported by 10 parents), peer influence, and parents’ busy schedules that reduce the amount of quality time available for spiritual education. However, children’s perceptions emphasize that parental role-modeling—through prayer, worship, and tangible expressions of love—has a profound and motivating impact. Children not only imitate religious practices but also internalize their faith when they experience loving relationships and spiritual consistency within the home. The study concludes that children’s faith formation requires a holistic and relational approach that integrates rituals, narratives, role-modeling, and warm communication within the family. These findings contribute insights for churches and policymakers in designing family-support programs that respond to the spiritual dynamics of younger generations in the digital era.